Adhesion between different asphalt binders and aggregate types evaluated using boiling water stripping test in scope of WMA foaming technique - Chomicz-Kowalska, Anna; Maciejewski, Krzysztof (International Conference “Environmental Engineering”, 2026)
This study examines adhesion mechanisms in binder–aggregate systems designed to simulate warm-mix asphalt incorporating water-foamed bitumen. The experimental program involved limestone, gabbro, melaphyre and quartzite aggregates, along with four paving-grade asphalt binders (50/70 and 45/80-55) originating from two different refineries. Adhesion performance was assessed using the boiling water stripping test, with residual binder coverage quantified through digital image analysis. In addition, dynamic viscosity measurements of the asphalt binders at relevant temperatures were conducted, and the petrographic analysis of the composition of aggregates was conducted. The samples produced with conventional (liquid) binders were mixed at temperatures representative of hot-mix asphalt production while reduced temperatures typical of warm-mix asphalt technology (20 °C lower) were used with the foamed asphalt binders. With the limestone and gabbro aggregates most of the experiments yielded over 90% residual binder coverage after the boiling test. The melaphyre and quartzite aggregates revealed on the other hand significant differences between the performance of the binders in terms of their type, origin and their form. The foamed binders with lowered mixing temperatures produced on average approx. 5% point lower residual binder coverage in melaphyre and quartzite while in limestone and gabbro the average difference was only 1% point. The source refinery of the asphalt binder significantly affected adhesion outcomes; however, the supplementary rheological and chemical analyses did not fully account for the observed discrepancies. Overall, the findings suggest that the foaming process itself may enhance the water resistance of asphalt binder-aggregate systems.